2006
DOI: 10.1249/01.mss.0000227311.00976.68
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cdc2 in Axonal Regeneration Enhanced by Exercise Training in Rats

Abstract: The present data suggest that Cdc2 kinase activated in the regenerating sciatic nerve may play an important role in TMT-mediated enhancement of axonal regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 26 publications
1
57
0
7
Order By: Relevance
“…Marqueste et al (2004) found that treadmill training after common fibular nerve transection and repair results in better mechano-and metabosensitive afferent recovery in rats (Marqueste, et al, 2004). A more recent report showed a positive effect of treadmill training on axon regeneration in rats after sciatic nerve crush (Seo, et al, 2006). However, this is the first study to provide direct evidence of a positive effect of post-injury exercise training on axon regeneration after peripheral nerve transection.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Marqueste et al (2004) found that treadmill training after common fibular nerve transection and repair results in better mechano-and metabosensitive afferent recovery in rats (Marqueste, et al, 2004). A more recent report showed a positive effect of treadmill training on axon regeneration in rats after sciatic nerve crush (Seo, et al, 2006). However, this is the first study to provide direct evidence of a positive effect of post-injury exercise training on axon regeneration after peripheral nerve transection.…”
Section: Discussionmentioning
confidence: 86%
“…Intensity was manipulated by altering treadmill speed. Continuous training has been used more extensively in animal exercise studies and has been applied in previous studies of exercise after peripheral nerve injury (Marqueste, et al, 2004, Seo, et al, 2006. However, the preferred approach to patterned running for rodents is brief intervals of high-intensity running interspersed with periods of rest (De Bono, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moderate exercise in the form of treadmill training has been shown to enhance axon regeneration following peripheral nerve injury in mice (English et al 2009;Sabatier et al 2008) and rats (Asensio-Pinilla et al 2009;Ilha et al 2008;Seo et al 2006;Udina et al 2011), but its full effects on functional recovery are not known. We hypothesized that moderate exercise in the form of daily treadmill training during the first 2 wk following transection and repair of the rat sciatic nerve would lead to improved functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In studies from our laboratory in mice (Sabatier et al 2008), exercise in the form of moderate daily treadmill training results in a marked enhancement of axon regeneration in cut nerves. Others have reported a variety of different training paradigms in different injury models (crush or transection) in rats that result in enhanced axon regeneration (Asensio-Pinilla et al 2009;Ilha et al 2008;Seo et al 2006;Udina et al 2011). We have used a combination of transgenic and knockout mice to show that the enhancement of axon regeneration produced by this moderate exercise is the result of an autocrine neurotrophin stimulation of regeneration of injured axons (Wilhelm et al 2012).…”
mentioning
confidence: 99%
“…Given that Cdc2 activation mediates cell proliferation and (Seo et al, 2006). Here we explored Cdc2 function in Schwann cells associated with nerve regeneration, and found that Cdc2 expression was induced in Schwann cells and promoted Schwann cell migration, which is functionally related to the nerve regeneration process.…”
Section: Introductionmentioning
confidence: 98%